Network capacity analysis for code propagation in Wireless Sensor Networks. (24th June 2011) - Mutluoglu, Mustafa Bulent; Baydere, Sebnem
Wireless Sensor Networks (WSN) monitor large environments for long periods of time. During this period, mechanisms are needed to propagate code updates to the network when needed. In this paper, a distributed code propagation algorithm that utilises reliable transport to all sensors is presented. A mathematical model is developed to analyse the achievable network branch capacities in terms of optimum node numbers per tree level. The outcome of the analysis is used to construct an optimum tree with heuristically best children lists. The capacity analysis is verified with experimental testbed and simulation results and the performance gain is shown.